FUNGSI KELUARGA TERHADAP PENGAMBILAN KEPUTUSAN REMAJA DALAM PEMILIHAN JURUSAN - Appulembang, Yeni Anna; Agustina, Agustina (STKIP Andi Matappa, 2020)
Adolescence is a period where their seems to be separated from the role of their parents and more independent in making their own decisions. But this time, the family plays a role in the behavior of adolescents in the decision making process, one of which is related to education in the selection of majors degree in university that will determine the future of their children. This research aims to determine the role of family support In adolescent for career decision making in major degree a in university. Causal comparative study was used and a sample 301 college student in grade one was selected through nonprobability sampling. This research was used two research tolls such as the role family was used Family Asessment Device (FAD) and decision making was used Career Decision-Making Profile. The result in this research found that score of the role of family based on mean hipotetic is lower than mean empiric. It means that, the role of family low category. In this research also showed the result used simple regression , F value 0.790 and p value 0.099 > 0.05. it means there is no significant the role of family support in adolescent for decision making in major degree in university.